2005
DOI: 10.1002/ana.20673
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquilin 1 polymorphisms are not associated with late‐onset Alzheimer's disease

Abstract: Several studies have reported evidence for linkage of late-onset Alzheimer's disease (LOAD) to chromosome 9. Recently, an intronic polymorphism affecting alternative splicing of exon 8 of ubiquilin 1 (UBQLN1) was reported to be associated with LOAD. We attempted to replicate this observation by genotyping this polymorphism, rs12344615 (also known as UBQ-8i), in a large sample of 1,544 LOAD cases and 1,642 nondemented controls. We did not find any evidence that this single nucleotide polymorphism, or any of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…An intronic polymorphism involving alternative splicing of exon 8 in the ubiquilin 1 gene (UBQLN1), which is genetically located near a well-established linkage peak for AD on chromosome 9q22, has been associated with increased risk for lateonset AD (Bertram et al 2005). However, this finding has not been replicated by others (Smemo et al 2006).…”
Section: Significance Of Ubiquitinated Neurofibrillary Tanglesmentioning
confidence: 99%
“…An intronic polymorphism involving alternative splicing of exon 8 in the ubiquilin 1 gene (UBQLN1), which is genetically located near a well-established linkage peak for AD on chromosome 9q22, has been associated with increased risk for lateonset AD (Bertram et al 2005). However, this finding has not been replicated by others (Smemo et al 2006).…”
Section: Significance Of Ubiquitinated Neurofibrillary Tanglesmentioning
confidence: 99%
“…Although the exact role of ubiquilin 1 is unknown, it is believed to promote the accumulation of PS1 full-length protein and regulate its endoproteolysis, whereas also modulating the levels of other members of the ␥-secretase complex such as pen2 and nicastrin (14,15). Although there are contradictory data from case-control studies present (16,17), it has recently been shown that genetic variants in UBQLN1 substantially increase the risk of developing AD (18 -20). In their family-based cohort study, Bertram et al (18) have shown that several single nucleotide polymorphisms in UBQLN1 are associated with AD, one of them (UBQ-8i) leading to alternative splicing of the gene in the brain.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…In a search for presenilin interactors, ubiquilin 1 was identified using yeast two-hybrid, colocalization and glutathione S-transferase pull-down assays (14). Moreover, it has recently been suggested that genetic variants in UBQLN1 may be associated with an increased risk of AD (18,19,20), although other studies could not confirm the association (16,17). Very little is known so far about the function of ubiquilin 1 in the brain.…”
Section: Tablementioning
confidence: 99%
“…As is often the case with gene variants exerting modest effects on disease risk, subsequent genetic studies have both supported (9,10) and not supported (11,12) the initial genetic finding. Further support for the candidacy of UBQLN1 as an AD risk gene will require a comprehensive assessment of the functional role of UBQLN1 in the key pathways relevant to AD pathogenesis.…”
mentioning
confidence: 99%